SEX DIFFERENCES IN THE ASSOCIATION BETWEEN PENTRAXIN 3 AND COGNITIVE DECLINE: THE CARDIOVASCULAR HEALTH STUDY. (11th November 2018) - Miller, L; Jenny, N; Rawlings, A; Arnold, A; Fitzpatrick, A; Lopez, O; Odden, M
Abstract: The importance of systemic inflammation, measured by C-reactive protein, in cognitive decline has been demonstrated; however, the role of vascular inflammation is less understood. We investigated the association between pentraxin 3 (PTX3), a novel marker of vascular inflammation, and changes in cognitive function. We followed adults 65 and older, free of cardiovascular disease (CVD) for up to 9 years (n = 1, 547) in the Cardiovascular Health Study. We used adjusted linear mixed effects models to evaluate the relationship between PTX3 and cognitive function, measured using the Modified Mini Mental State Examination (3MSE). Mediation by CVD events, and effect modification by sex and apolipoprotein E ɛ4 allele (APOE) were also examined. The average annual decline in 3MSE was 0.14. The association between PTX3 and change in 3MSE differed between women and men (p = 0.02). In the adjusted model, each standard deviation higher in PTX3 was associated with a 0.20 greater rate of decline in 3MSE score per year in women over follow-up (95% CI: -0.37, -0.03; p = 0.02), compared no change in rate of decline in men (β = 0.07; 95% CI: -0.08, 0.22). Adjustment for mediating CVD events had a minor effect on the associations. No effect modification by APOE was found. In this population-based prospective cohort study of older adults, we found that vascular inflammation was significantly associated with cognitive decline in women.